Karampetakis, Nicholas - (:unkn) unknown (My University, 2026)
Nicholas P. Karampetakis was born in Drama, Greece in 1967. He received the bachelor degree in Mathematics and Ph.D. in Mathematics from the Department of Mathematics, Aristotle University of Thessaloniki, Greece in 1989 and 1993 respectively. From November 1994 to September 1995 he was a research associate with the Department of Mathematical Sciences, Loughborough University of Technology, England. From September 1995 to March 1999 he was a Research Associate with the Department of Mathematics, Aristotle University of Thessaloniki, Greece. From August 2000, to July 2009 he was an Assistant Professor to the same Department, whereas from July 2009, to August 2014 he was an Associate Professor. Since August 2014 he has been Professor in Control Systems Theory in Department of Mathematics, whereas from September 2013 till the end of August 2017 is the Head of Department of Mathematics of the Aristotle University of Thessaloniki, Greece. During the above periods he received many fellowships from the Greek Government, British Council and Engineering and Physical Sciences Research Council of England, and contributes in many research projects sponsored by the Greek Government and the European Union. His present research interests lie mainly in algebraic methods for computer aided design of control systems (CACSD), numerical and symbolic algorithms for CACSD, polynomial matrix theory and issues related to the mathematical systems theory. Dr. Karampetakis is a frequent contributor to the field in the form of journal articles, conference presentations and reviews. He is is a Senior Member of IEEE and a vice-Chair of the IEEE Action Group on Symbolic Methods for CACSD. He is also an Associate Editor a) of the Journal of Multidimensional Systems and Signal Processing and b) of the International Journal of Applied Mathematics and Computer Science.